The Effect of Kangaroo Care and Breastfeeding on Reducing the Pain due to Hepatitis B Vaccine Injection in Newborn Infants: A Comparative Analysis - Tuğba Karakuş Türker; Duygu Gözen (Galenos Yayinevi, 2022)
Aim:This study was conducted to compare the effects of breastfeeding (BF) and kangaroo mother care in newborns on the level of pain and physiological changes due to an injection of the hepatitis B vaccine.Materials and Methods:This study was designed as a comparative experimental study. The sample of this study consisted of a total of 70 infants, including 35 in the Kangaroo group and 35 in the BF group, who were followed up in the postnatal ward at Zeynep Kamil Training and Research Hospital between August 2016 and February 2017 and who also met the sample criteria. The pain levels, duration of crying, heart rates (HR) and oxygen saturation (SpO2) of the newborn infants were compared before and after a hepatitis B vaccine injection.Results:It was determined that there was no statistically significant difference between the infants in the BF and kangaroo mother care groups in terms of their pain scores (Z=0.949; p=0.343), SpO2 levels (Z=1.032; p=0.302), HR (Z=0.206; p=0.837) and duration of crying (Z=0.135; p=0.892). Following the vaccination, the HR and pain scores of the infants in the BF gruop increased by less and they had a shorter duration of crying.Conclusion:According to these results, BF infants is effective in reducing the pain induced by invasive interventions as this is easily applicable, takes little time, encourages breast milk and strengthens the mother-infant attachment.